PENGARUH PELAYANAN DAN DAYA TARIK PRODUK TERHADAP KEPUASAN NASABAH KREDIT UMUM BANK EKA BUMI ARTHA KOTA METRO - Karnila Ali (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Method used in this research was explanatory survey. It was a quantitative research with service, product appeal, and customer satisfaction as the object. The research population was Eka Bumi Arta Bank Metro City customers with a total sample of 80 customers taken by accidental sampling technique. The decision making of the analysis-based research result was using multiple linear regression analysis. The research is to analyze the effect of service and product appeal on satisfaction of general credit customers at Eka Bumi Artha Bank Metro City. It was a descriptive qualitative research, a research procedure that produces descriptive data based on the result of quantitative analysis of research variables. Data collection techniques used were interview, documentation, and questionnaire. Analytical tool used was data quality analysis and multiple linear regression analysis. The conclusion is that the service analysis result has a significant effect on customer satisfaction. Product appeal has a significant effect on customer satisfaction. In addition, Service and Product Appeal simultaneously have a significant effect on customer satisfaction. It can be said that the independent variables have a positive and significant effect on customer satisfaction based on these results. Keywords : Service, Product Appeal, Customer Satisfaction.